Measuring the impact of climate change on Indian agriculture - Dinar, Ariel; Dinar, Ariel (Washington, D.C. World Bank, 1998)
This report provides information on a series of associated analyses done on how climate change impacts on the agricultural system in India. The analysis features the Ricardian approach which compares agricultural outcomes across farms under different climate conditions. Following an introduction, Chapter 2 provides an extensive literature review that includes studies addressing climate change impacts on sectors other than agriculture. In Chapter 3 several Global Change Models (GCMs) are employed to provide a range of temperature and rainfall values that may result from predicted changes in carbon dioxide levels in the future. Results from these GCM models are used later for simulation of Ricardian models ' results. Each of the Ricardian studies emphasize a different methodology. The pooled data analysis (Chapter 4) examines long run response of farms to climate by Indian farming districts. The year by year analysis (Chapter 5) explains annual fluctuations in climate sensitivity by using regressions of a cross section of Indian agricultural districts for several years. This analysis measures how climate sensitivity varies from year to year in response to several variables, including prices and weather. The climate-technology study (Chapter 6) of Indian districts explores the role endogenous technology plays on farmer ' s climate sensitivity. The analysis examines whether technology has altered climate sensitivity and whether climate change might alter technical change.
Includes bibliographical references.
Keywords: Climatic changes -- India; Crops and climate -- India; Agriculture -- India